The F# Language Design RFCs (F# 6.0) - Syme, Don (Web, 2021)
The F# Language is a co-operation between the F# Community including contributors from Microsoft, Microsoft Research and Github. The RFCs for F# 6.0 have been developed by Don Syme, Phillip Carter and others and are available here: fslang-design/FSharp-6.0 at main · fsharp/fslang-design · GitHub
The F# Language is a co-operation between the F# Community including contributors from Microsoft, Microsoft Research and GitHub.